The v‐DECAF score can predict 90‐day all‐cause mortality in patients with COPD exacerbation requiring invasive mechanical ventilation. (22nd April 2019) - Shi, Qi‐fang; Sheng, Ying; Zhu, Nian; Tan, Yan; Xie, Xiao‐Hong; Wang, Shu‐yun; Cai, Jin‐fang
Abstract: Introduction: The DECAF score is a simple and effective tool for predicting mortality in patients hospitalized with acute exacerbations of chronic obstructive pulmonary disease (AECOPD); however, the DECAF score has not been validated in AECOPD patients requiring invasive mechanical ventilation (IMV). We devised the ventilator (v)‐DECAF score, in which "anemia" replaces "acidaemia, " for use in AECOPD patients requiring IMV. The objective of this study was to compare the predictive efficacy of the v‐DECAF score and the DECAF score. Methods: This study prospectively recruited 112 consecutive AECOPD patients requiring IMV from a single center. The clinical endpoint was 90‐day all‐cause mortality. Demographic and clinical data were recorded, as well as APACHE II, GCS, CURB‐65, BAP‐65 and DECAF scores, and the newly devised v‐DECAF score. The discriminatory value of the scoring systems in predicting 90‐day all‐cause mortality was determined using the area under the receiver operating characteristic (AUROC) curve. Results: In multivariate logistic regression analysis, the v‐DECAF score was an independent predictor of 90‐day all‐cause mortality (odds ratio 3.004, 95% CI 1.658‐5.445, P < 0.001). The AUROC of the v‐DECAF and DECAF scores were 0.852 (95% CI 0.766‐0.938) and 0.777 (95%CI: 0.676‐0.878), respectively. The v‐DECAF score had a better predictive value for 90‐day all‐cause mortality compared to the DECAF score ( Z = 2.338, P = 0.019). Conclusion: The v‐DECAF score had good discriminatory power in predicting 90‐day all‐cause mortality in AECOPD patients requiring IMV.